2019
DOI: 10.1071/es19009
|View full text |Cite
|
Sign up to set email alerts
|

Using global navigation satellite system data for real-time moisture analysis and forecasting over the Australian region I. The system

Abstract: The use of high spatial and temporal resolution data assimilation and forecasting around Australia’s capital cities and rural land provided an opportunity to improve moisture analysis and forecasting. To support this endeavour, RMIT University and Geoscience Australia worked with the Bureau of Meteorology (BoM) to provide real-time GNSS (global navigation satellite system) zenith total delay (ZTD) data over the Australian region, from which a high-resolution total water vapour field for SE Australia could be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…where ϕ and H are the latitude ( • ) and height (km) above the reference ellipsoid of the site, respectively. The zenith wet delay (ZWD) over the GNSS station is then obtained from subtracting the ZHD from the ZTD, then the ZWD is converted to GNSS-PWV (mm) using the following formula [32]:…”
Section: Retrieval Of Gnss-pwvmentioning
confidence: 99%
See 1 more Smart Citation
“…where ϕ and H are the latitude ( • ) and height (km) above the reference ellipsoid of the site, respectively. The zenith wet delay (ZWD) over the GNSS station is then obtained from subtracting the ZHD from the ZTD, then the ZWD is converted to GNSS-PWV (mm) using the following formula [32]:…”
Section: Retrieval Of Gnss-pwvmentioning
confidence: 99%
“…Nowadays, many regional and global GNSS networks, which consist of various numbers of tracking stations, are available. This makes the best use of GNSS data for studies and applications on short-term weather predictions feasible and meaningful [17,[30][31][32], in addition to facilitating climate change research [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…over seven domains: Perth (PH), Adelaide (AD), Victoria-Tasmania (VT), Sydney (SY), Brisbane (BN), Darwin (DN), and North Queensland (NQ), as shown in Figure 1 . It has a variable horizontal resolution grid with fixed 1.5 km resolution inner domain, stretching to 4 km at the outer boundary, and 80 vertical levels up to 40 km, with the lowest model level at 2.5 m. In this study, we focus on the Sydney domain, shown in blue (outer) and green (inner) in Figure 1 [ 14 , 15 , 16 ]. The variational assimilation system uses the observations and the background model short-range forecast from the previous cycle to generate an analysis increment.…”
Section: System Configuration and Methodsmentioning
confidence: 99%
“…In this study, Victoria, located in southeastern Australia, is selected as the study region. Although it is the second smallest state in Australia, it has a varied climate with frequent occurrences of severe weather events, e.g., rainstorms, tropical cyclones, and extreme floods [40], [41], [42]. According to statistics, severe weather events happened in the state of Victoria alone have caused over $1.9 billion economic loss and have also greatly affected more than 2.5 million people over the past 20 years [43], [44].…”
Section: A Study Region and Periodmentioning
confidence: 99%